(untitled) - Schmitz, John E. J. (Norwich, NY, 2007)
Entropy explains the amount of energy no longer capable of conversion into work; in other words, wasted energy or heat loss. This book refers to the second law of thermodynamics, entropy,...
Keywords: Entropy,Thermodynamics,Nhiệt động lực học